Barriers to Recruiting an Adequate Sample in Rural Nursing Research - Shirley Cudney; Carol Craig; Elizabeth Nichols; Clarann Weinert (Rural Nurse Organization; Binghamton University, 2004)
Recruiting an adequate sample in rural nursing research has its unique challenges. In this article, nurse researchers share their adventures in recruiting study participants from four studies in the rural West. Distilled from these adventures, the authors present several issues to consider when developing recruitment strategies as part of the overall planning of a rural study. These include: (a) uniqueness of the rural culture and context, higher costs of recruitment, (b) necessity for rural-sensitive recruitment materials, (c) over-sampling, and (d) lack of local research infrastructure.